Access and Use of DIKSHA for School Teachers and Students Amid COVID-19: An Assessment of Rural Rajasthan - Verma, Ratna; Dash, Debendra Nath; Purohit, Mahima (Indian Journal of Educational Technology, 2025)
The COVID-19 pandemic has led to unprecedented disruptions in education worldwide. With the closure of schools, the entire focus of the education system shifted to digital education. The study assessed the access and use of the online education platform DIKSHA during the pandemic in rural areas of Rajasthan. It employed mixed methods research and covered 100 government schoolteachers and 100 students of grades 9-12. The study findings indicate that 96 per cent of teachers learnt to use DIKSHA during a pandemic and used the portal for lesson plans, assessments, question banks, and improving teaching skills. 95 per cent of students used DIKSHA to access digital textbooks and interactive worksheets. Education through DIKSHA has bridged the learning gap among rural children during the pandemic. The study also assessed challenges faced by teachers and students related to internet connectivity and interruptions.